2008
DOI: 10.1111/j.1365-2850.2008.01268.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to animal‐assisted therapy with farm animals among health staff and farmers

Abstract: Green care is a concept that involves the use of farm animals, plants, gardens or the landscape in cooperation with health institutions for different target groups of clients. The present study aimed at examining psychiatric therapists' (n = 60) and farmers' (n = 15) knowledge, experience and attitudes to Green care and animal-assisted therapy (AAT) with farm animals for people with psychiatric disorders. Most respondents had some or large knowledge about Green care, but experience with Green care was generall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 9 publications
2
49
0
8
Order By: Relevance
“…Most commonly, these are group activities, but they should always be adapted to each individual participant's mental and physical needs. Several studies on care farming highlight group participation, the social setting, and the farmer's supportive supervision as important [20][21][22][23]. Furthermore, earlier qualitative studies have described care farming programs as a suitable transition between marginalization related to illness and inclusion in society [22,24].…”
Section: Introductionmentioning
confidence: 99%
“…Most commonly, these are group activities, but they should always be adapted to each individual participant's mental and physical needs. Several studies on care farming highlight group participation, the social setting, and the farmer's supportive supervision as important [20][21][22][23]. Furthermore, earlier qualitative studies have described care farming programs as a suitable transition between marginalization related to illness and inclusion in society [22,24].…”
Section: Introductionmentioning
confidence: 99%
“…En cuanto a las variables personales que pueden influir sobre la actitudes hacia las IAA, sólo el sexo del respondiente contó con apoyo empírico en la literatura previa, en la que son descritas expectativas más positivas en mujeres que en varones (Berget et al, 2008;Berget y col., 2011). Otras variables de interés estudiadas, como la experiencia con animales domésticos y/o de granja, la experiencia en intervenciones asistidas, el interés por participar en IAA o la profesión desempeñada no han mostrado una relación consistente en la literatura previa (Berget y col., 2011; López-Cepero, Perea-Mediavilla, Sarasola y Tejada, 2015; Moody et al, 2002;Perea-Mediavilla, López-Cepero, Tejada y Sarasola, 2014).…”
Section: Introductionunclassified
“…A qualitative study among 13 psychotherapists using AAT with dogs, found that the majority of the therapists ranked anxiety disorders as one of the diagnoses that profited most on AAT (Mason & Hagan, 1999). Another study by Berget et al (2008b) examining 60 psychiatric therapists' knowledge, experience and attitudes to Green care and AAT with farm animals for people with psychiatric disorders, showed that most of the therapists thought that AAT with farm animals contributed to increased skills in interactions with other humans. Two-thirds of the therapists believed that AAT with farm animals to a large extent could contribute better to mental health than other types of occupational therapy.…”
Section: Attitudes To Animal-assisted Interventions Among Therapistsmentioning
confidence: 99%